The Effect of Firm- and Industry-Level Contracts on Wages: Evidence from Longitudinal Linked Employer-Employee Data - Nicole Gürtzgen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Using a large linked employer-employee data set, this paper presents new evidence on the wage premium under collective bargaining contracts in western and eastern Germany. The novel feature of our analysis is that we use a longitudinal data set. In contrast to previous studies, we seek to assess the extent to which differences in wages between workers in covered and uncovered firms arise from the non-random selection of workers and firms into the different regimes. By measuring the relative wage gains or losses of workers employed in firms that change contract status, we obtain estimates that depart considerably from previous results relying on cross-sectional data. Industrylevel contracts in western Germany and firm-level contracts in eastern Germany are associated with a small, but statistically significant average wage premium of about 2 per cent. Finally, results from a trend-adjusted differencein - difference approach indicate that the industry-level wage premium in western Germany might be downward biased and the firm-level premium in eastern Germany might still be upward biased, once differences in pre-transition wage growth are accounted for.
Older version: http://hdl.handle.net/10419/24537
Keywords: J51; J31; 330; Union Wage Premium; Collective Bargaining Coverage